2011
DOI: 10.1007/s00276-011-0814-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the medial collateral ligament and the medial meniscus: a topographical and biomechanical study

Abstract: The functional influence of the medial collateral ligament on the medial meniscus is still discussed controversially. Commonly, a strong fixation of the meniscus by the collateral ligament is described. Injury to the medial meniscus is explained by its reduced mobility due to its strong adherence to the medial collateral ligament. The analysis of 10 plastinated series of the medial femorotibial compartment prove that only few fibres of the ligament radiate into the meniscus. To define the possible contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…In their experimental study on two cadavers, Stein et al [12] concluded that there was “no relevant influence of the medial collateral ligament on the stability of the medial meniscus”. The Stein study applied a 500 N compressive load to intact knees and after detaching the medial collateral ligament from the femur.…”
Section: 0 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their experimental study on two cadavers, Stein et al [12] concluded that there was “no relevant influence of the medial collateral ligament on the stability of the medial meniscus”. The Stein study applied a 500 N compressive load to intact knees and after detaching the medial collateral ligament from the femur.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Anatomical studies of the dMCL have separated it into two functional units, the meniscofemoral and meniscotibial divisions, with stout attachments to the meniscus described [11]. But, in a recent study, Stein et al did not measure any differences in tibial plateau stress after transecting the dMCL meniscal attachments on two cadaver knees loaded with a 500 N axial force, concluding that the dMCL did not affect the stability of the medial meniscus [12]. …”
Section: 0 Introductionmentioning
confidence: 99%
“…al. concluded that the medial collateral ligament did not affect the stability of the medial meniscus (Stein, Koebke et al 2011). The anterior intermeniscal ligament (AIML) was included in our models.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the latter has some fibers mixing with the anterior cruciate ligament (ie, histologic continuum) . An anatomic detail of considerable clinical relevance would be that the medial meniscus shares fibers with the MCL near its capsular attachment . The histologic architecture of meniscal tissue consists of cells suspended in an extracellular matrix of collagen, proteoglycans, glycoproteins, and elastin .…”
mentioning
confidence: 99%
“…2 An anatomic detail of considerable clinical relevance would be that the medial meniscus shares fibers with the MCL near its capsular attachment. 3 The histologic architecture of meniscal tissue consists of cells suspended in an extracellular matrix of collagen, proteoglycans, glycoproteins, and elastin. 4 A perimeniscal capillary plexus, originating in the capsular and synovial tissues of the knee joint (from the medial geniculate arteries), supplies the peripheral portion of the medial meniscus through penetrating radial vessels.…”
mentioning
confidence: 99%